Pengaruh Inovasi Pembelajaran Melalui Aplikasi Canva Dan Wordwall Terhadap Hasil Belajar PAI Di SMP Islam Nurul Hikmah Pesisir Besuki Situbondo - Akilla, Hamidah; Zakiyah BZ (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of learning innovation through the Canva and Wordwall applications on Islamic Religious Education (PAI) learning outcomes at SMP Islam Nurul Hikmah Pesisir Besuki Situbondo. The background of this research is based on the low interest and learning outcomes of students in PAI subjects, which is suspected to be caused by the lack of variation in teaching methods used by teachers. The research method used is quantitative with a quasi-experimental design, involving two groups: an experimental class using Canva and Wordwall, and a control class using conventional methods. The research instrument was a learning outcome test administered before and after the treatment (pre-test and post-test). Data analysis results showed a significant improvement in the learning outcomes of students in the experimental class compared to the control class. These findings indicate that the use of Canva and Wordwall applications in learning can effectively improve students’ PAI learning outcomes. Thus, digital-based learning innovations are feasible to be integrated into the PAI learning process in schools.